Lineabilidade e espaçabilidade em conjuntos de operadores que atingem a norma e em espaços de sequências - Câmara., Kleber Soares (2012)
The notion of lineability emerged in the eighties, albeit its essence is quite older, as a method to measure the existence of linear structures in a priori nonlinear frameworks. More precisely, a subset of a topological vector space is lineable (spaceable) if it contains, except eventually for the null vector, an infinite-dimentional subspace (infinite- dimensional closed subspace). In this work we investigate lineability and spaceability in the context of norm attaining operators and sequence spaces.